Design of a dynamometer-engine coupling shaft / Mohd Hasnun Arif Hassan - Mohd Hasnun , Arif Hassan (2012)
In measuring the power output of an engine, the engine has to be coupled to a load device known as dynamometer. The coupling is done by means of a solid shaft. The proper couplings and shaft are required for the connection to avoid any failure to the engine or the dynamometer. Unsuitable selection could lead to undesired problems such as torsional vibrations, vibration of the engine and dynamometer, whirling of the coupling shaft, damage of the bearings, engine starting problem or immoderate wear of the shaft line components. The commonly encountered problem is the resonance in torsional vibration, which results in disastrous failure of the shaft due to excessive vibration. This project is aimed to study the appropriate design of the shaft to be used in the dynamometer-engine coupling to prevent the system from undergoing unwanted problems. The theoretical calculations involve in the design are presented. The dimension of the coupling shafts for engines with various maximum torques are estimated. It is shown that the diameter of the shaft is proportional to the maximum torque of the engine given that the same coupling is used for every system, whereas the length of the shaft is almost equal for every engine. The diameter of the shaft is a vital parameter compared to its length. For engines with the maximum torque vary from 40 to 200 Nm, the same shaft length of 500 mm can be used but with increasing shaft diameter as the maximum torque increases. For a 40 Nm engine, the shaft diameter of 20 mm generated acceptable result. The shaft diameter was increased by 5 mm as the maximum torque increases and acceptable results were obtained. On the other hand, by using aluminium instead of steel as the material of the shaft, lower critical engine speed is obtained given that the same dimension of the shaft is used. This is due to the fact that aluminium possesses lower modulus of rigidity in comparison to steel.